The Role of Green Bonds as a Financing Solution for Adapting to ESG Regulations and Its Impact on Corporate Profitability - Riswanda, Muhammad Rumi Alvito; Precilia, Tharisa; Tjajadi, Catherine; Fauzi, Fitriya (International Journal of Finance Research, 2025)
The article